Impulsive choice behavior in four strains of rats: evaluation of possible models of Attention Deficit/Hyperactivity Disorder - Garcia, Ana; Kirkpatrick, Kimberly (My University, 2013)
Several studies have examined impulsive choice behavior in spontaneously hypertensive rats (SHRs) as a possible pre-clinical model for Attention-Deficit/Hyperactivity Disorder (ADHD). However, this strain was not specifically selected for the traits of ADHD and as a result their appropriateness as a model has been questioned. The present study investigated whether SHRs would exhibit impulsive behavior in comparison to their control strain, Wistar Kyoto (WKY) rats. In addition, we evaluated a strain that has previously shown high levels of impulsive choice, the Lewis (LEW) rats and compared them with their source strain, Wistar (WIS) rats. In the first phase, rats could choose between a Smaller-sooner (SS) reward of 1 pellet after 10 s and a Larger-later (LL) reward of 2 pellets after 30 s. Subsequently, the rats were exposed to increases in LL reward magnitude and SS delay. These manipulations were designed to assess sensitivity to magnitude and delay within the choice task to parse out possible differences in using the strains as models of specific deficits associated with ADHD. The SHR and WKY strains did not differ in their choice behavior under either delay or magnitude manipulations. In comparison to WIS, LEW showed deficits in choice behavior in the delay manipulation, and to a lesser extent in the magnitude manipulation. An examination of individual differences indicated that the SHR strain may not be sufficiently homogeneous in their impulsive choice behavior to be considered as a viable model for impulse control disorders such as ADHD. The LEW strain may be worthy of further consideration for their suitability as an animal model.
Keywords: Impulsive choice; Impulse control; Differences among rat strains; Attention Deficit/Hyperactivity Disorder; Individual differences